PENERAPAN KONSEP LEAN SIX SIGMA UNTUK MENINGKATKAN KUALITAS PRODUKSI KNALPOT RACING “PROLINER” - Michael Kartawijaya; Mohammad Agung Saryatmo; Ahmad (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
Quality is an important factor in determining business success, poor quality can cause consumers to look for other products. Good product quality depends on a good production process between human factors, machines, and the methods used. But it is undeniable that these factors are also a waste in a production process and have an effect on the production results produced. This study aims to improve production quality and reduce defect levels in the exhaust manufacturing process at PT. GKS. The main problem faced by the company is the high defect rate, averaging 5.71% during the period of October 2024 to August 2025. The dominant defects include dented silencers, damaged pipes, cracked bowls, and drilling defects. To address this issue, the research applied the Lean Six Sigma methodology through the DMAIC (Define, Measure, Analyze, Improve, Control) as an error-proofing system. The results of the 2-week implementation study showed that the Defects Per Million Opportunities value (DPMO) decreased from 57,075 to 56,455, and the sigma level improved from 3.07 to 3.79, DPMO value decreased from 57.075 to 56.455, the sigma value increased from 3.07 to 3.79, and the process efficiency (PCE) increased from 46.15% to 49.2%indicating a significant enhancement in production process quality. The implementation of improvement measures such as production checksheets, One Point Lessons (OPL), and operator training successfully reduced defects and increased efficiency. Overall, the application of Lean Six Sigma proved effective in minimizing waste, stabilizing processes, and improving product quality at PT. GKS.